Completing the genetic puzzle of the reed warbler complex: insights from Italy. Issue 4 (1st October 2020) - Ilahiane, Luca; Boano, Giovanni; Pavia, Marco; Pellegrino, Irene; Grussu, Marcello; Voelker, Gary; Galimberti, Andrea
ABSTRACT: Capsule: Analysis of mitochondrial DNA from reed warblers sampled in Italy reveals that they are most similar to the nominate race of European Reed Warbler Acrocephalus scirpaceus scirpaceus . Aim: To fill gaps in our knowledge of the distribution of European/African Reed Warblers Acrocephalus scirpaceus/baeticatus in the Mediterranean region through genetic analysis of populations from the key biogeographic areas of Sicily, Sardinia and mainland Italy. Methods: We assessed the genetic placement of Italian reed warbler populations within a comprehensive dataset of this species complex, by sampling these birds from principal peninsular and insular breeding populations (for a total of 17 samples) and by comparing their mitochondrial cyt b sequences with those available in GenBank-NCBI. Results: The final dataset included 171 cyt b sequences (763 base pair long). The analysis showed samples from Italy had a high similarity with the European Reed Warbler A. s. scirpaceus subspecies. This fills an important information gap in the phylogeography of the group. Conclusion: The genetic cohesion shown between Italian and other European populations may denote a structuring in at least three distinct refugia in the Western Palearctic: Iberia for A. baeticatus ambiguus, the Caucasus Mountains for A. s. fuscus, and both Italy and the Balkans for A. s. scirpaceus .